PENGUATAN DAN KEBERLANJUTAN LPD MELALUI PENERAPAN ENVIRONMENTAL SOCIAL GOVERNANCE (ESG) - Ida Ayu Putu Widani Sugianingrat; Cokorda Gede Bayu Putra; Ni Wayan Alit Erlina Wati; I Wayan Arik Suwitra; I Made Roni Armajaya (JURNAL SEWAKA BHAKTI, 2023)
The Batur Village Credit Institution is a pilot LPD in Kintamani District that was able to grow and develop during the pandemic. Batur as a barometer of the economy in Kintamani District should be able to become a model for LPDs by other areas in Wingkang Ranu so that it is felt necessary to strengthen its economic institutions. The purpose of this service activity is to increase the ability and knowledge of LPD managers and oversight bodies in an effort to implement ESG and increase understanding in implementing ESG practice strategies at LPD Batur. The method used is in the form of lectures by inviting resource persons who are experts in the application of ESG at LPD Batur as well as conducting outreach and assistance in implementing ESG practices in savings and lending activities at LPD Batur. The results of this community service activity increase the ability and knowledge of LPD managers and supervisory bodies to increase in efforts to implement ESG. Furthermore, through the socialization program provided, increasing the understanding of LPD managers and supervisory bodies in implementing ESG practice strategies at LPD Batur. It is hoped that LPD managers and supervisory bodies can consistently apply ESG and community service activities can have a positive impact on LPD Batur customers, where LPD managers and supervisory bodies can implement strategies for sustainable ESG practices at LPD Batur.